2013
DOI: 10.3390/rs5104819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Land Surface Models in Reproducing Satellite-Derived LAI over the High-Latitude Northern Hemisphere. Part I: Uncoupled DGVMs

Abstract: Leaf Area Index (LAI) represents the total surface area of leaves above a unit area of ground and is a key variable in any vegetation model, as well as in climate models. New high resolution LAI satellite data is now available covering a period of several decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 50 publications
6
114
2
Order By: Relevance
“…However, the effect of CO 2 on soil moisture is unlikely to be a significant source of uncertainty in the context of this study as Leipprand and Gerten (2006) showed, using simulations from LPJ, that a doubling of CO 2 leads to only 1 % increase in soil moisture. Orchidee, LPJ and OCN are obtained from the TRENDY consortium (Sitch et al 2013, Murray-Tortarolo et al 2013. Simulations from their S3 set-up were considered, which are driven with carbon dioxide from ice core and NOAA, historical climate forcing from CRU and NCEP, and land use change from the HYDE database (Hurtt et al 2011).…”
Section: Observational Estimatesmentioning
confidence: 99%
“…However, the effect of CO 2 on soil moisture is unlikely to be a significant source of uncertainty in the context of this study as Leipprand and Gerten (2006) showed, using simulations from LPJ, that a doubling of CO 2 leads to only 1 % increase in soil moisture. Orchidee, LPJ and OCN are obtained from the TRENDY consortium (Sitch et al 2013, Murray-Tortarolo et al 2013. Simulations from their S3 set-up were considered, which are driven with carbon dioxide from ice core and NOAA, historical climate forcing from CRU and NCEP, and land use change from the HYDE database (Hurtt et al 2011).…”
Section: Observational Estimatesmentioning
confidence: 99%
“…Consequently, phenology shifts may feedback on climate with unclear magnitude and sign (Anav et al, 2013;MurrayTortarolo et al, 2013;Peñuelas et al, 2009). As a result of the significant changes that are already affecting the structure and function of Arctic ecosystems, it is critical to understand and quantify the C dynamics of the terrestrial tundra and taiga and their responses to climate change (McGuire et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, terrestrial biosphere models tend to have large uncertainties, for example, in phenology (Richardson et al, 2012;Murray-Tortarolo et al, 2013) and in spatial distributions of plant species (Cheaib et al, 2012). Recently, data assimilation (DA) methods which incorporate observation data into models have been applied to terrestrial biosphere models to reduce the uncertainties in the state variables and model parameters Peng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%